Test-case generation for embedded simulink via formal concept analysis - He, N; Ruemmer, P; Kroening, D (Association for Computing Machinery, 2011)
Mutation testing suffers from the high computational cost of automated test-vector generation, due to the large number of mutants that can be derived from programs and the cost of generating test-cases in a white-box manner. We propose a novel algorithm for mutation-based test-case generation for Simulink models that combines white-box testing with formal concept analysis. By exploiting similarity measures on mutants, we are able to effectively generate small sets of short test-cases that achieve high coverage on a collection of Simulink models from the automotive domain. Experiments show that our algorithm performs significantly better than random testing or simpler mutation-testing approaches.